Vibrações induzidas por vórtice em um cilindro com um grau de liberdade e rigidez não linear - Bastos, Sérvio Túlio Suenai Haramura [UNESP]; Vasconcellos, Rui Marcos Grombone de [UNESP]; Marques, Flávio Donizeti (My University, 2019)
In this research project, it is proposed an investigation of the effects of hardening structural nonlinearity in a single degree of freedom cylinder exposed to a transverse flow, presenting the vortex induced vibration effect. To check the validity of the implemented phenomenological model, numerical simulations has been performed and the results has been compared with experiments. Simulations showed that the presence of this type of nonlinearity extends the lock-in region by changing the structural natural frequency with the freestream speed and the vortex shedding frequency. A wind tunnel test validated the obtained simulated results. The contributions of this research can be helpful in order to prevent vortex induced vibrations in realistic nonlinear structures.
Keywords: Aeroelasticidade; Cilindros; Dinâmica estrutural